Analisis Struktur Jenis Kalimat Tunggl Dan Kalimat Majemuk Di Headline Radar Karawang Sebagai Pemanfaatannya Sebagai E-Modul - Rachmawati, Fannisa; Maspuroh, Uah; Adham, M. Januar Ibnu (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to describe single sentences and compound sentences in headlines in the March 2023 edition of Radar Karawang newspaper. The subjects of this research are 21 news headlines in the March 2023 edition of Radar Karawang. The object follows up the analysis of Radar Karawang newspaper by classifying the structure of single sentences and compound sentences. Then, the data collection technique used in this research is note taking technique. The researcher conducts 3 stages of data analysis, namely the preparation stage, the implementation stage and the completion stage. Then, the researcher uses data analysis techniques, namely, data reduction, preparation and verification. The researcher used the description method with a qualitative approach, with the aim of obtaining a description to find findings that will be described and describe the results of the analysis. The result of this research found 21 Headline Titles in the March 2023 Edition of Radar Karawang print mass media obtained 124 sentences, from all of these sentences there are 79 single sentences, 29 equivalent compound sentences and 16 multilevel compound sentences. However, in mixed compound sentences, the researcher did not find any type of mixed compound sentences in the headlines of Radar Karawang. This research can be utilized in teaching materials in the form of e-modules for junior high school level, especially class VIII, to facilitate the learning process.